Teleologie und politische Vernunft - Maier, Eva Maria (2002)
This book describes stages of development of the conception of an ideal republic that is fundamentally based on practical reason. It is widely understood that this conception is paradigmatically represented in the political thought of Aristotle and conveyed by its reception by Thomas Aquinas. This early concept of a liberal republic - which is in some ways certainly marked by the constraints of ancient philosophy on the whole, is even considered to have contributed to the development of the modern state and its instruments of political reason. Part 1 presents Aristotle's conception of "civil society" which is built upon man in his specific nature of humanity. From this point of view "political" government is intrinsically related to the mutual recognition of free and equal fellow citizens. Thus establishes a strict standard of criticism of any arbitrary or illegitimate presumption of political power. Nevertheless, Aristotle's "Republic" relies on limiting conditions of political subsistence as they arise from a specific ancient point of view that sets a clear limit to our modern expectation of freedom and equality. Above all, subjectivity, at least the perfection of virtuous citizenship, is supposed to be indispensably linked to a specific political, institutional and moral framework. This framework is derived from Aristotle's concept of "teleology", which pervades his whole philosophy. Therefore, Aristotle's approach shall be investigated in a most complex and comprehensive way in its close systematic link to all fields of philosophy, including practical reason, physics and metaphysics, in order to enable a most distinct historical judgement that will also finally reveal its actual significance. E.g. Aristotle's concept of teleology, though introduced by the investigat ...